Urgensi Penegakan Hukum Tindak Pidana Korupsi dalam Membangun Ketertiban Hukum - Rismarito Manik; Mey Enda Sinuraya; Chacha Widya Permata Sari; Ribet Sri Pipit Putri Zega; Cindy Laura Sihombing (Verdict: Journal of Law Science, 2026)
Corruption is an extraordinary crime that has developed systematically and poses serious threats to social stability, economic development, and legal order in Indonesia. Therefore, effective law enforcement against corruption crimes is an urgent necessity to uphold the rule of law, ensure justice, and build a stable legal order within society and the state. This study aims to analyze the urgency of law enforcement against corruption crimes as well as the challenges encountered in its implementation in Indonesia. The research employs a normative juridical method with statutory and conceptual approaches. The findings reveal that law enforcement in corruption cases continues to face several obstacles, including weak coordination among law enforcement institutions, inconsistency in legal enforcement, and inadequate oversight mechanisms. These conditions adversely affect legal order and undermine public trust in the legal system. Accordingly, strengthening an integrated, consistent, and accountable law enforcement system is a fundamental prerequisite for building a just and effective legal order.